NO-Donating NSAIDs, PPARδ, and Cancer: Does PPARδ Contribute to Colon Carcinogenesis?. (29th May 2008) - Mackenzie, Gerardo G.; Rasheed, Shaheen; Wertheim, William; Rigas, Basil
Abstract : The chemopreventive NO-donating NSAIDs (NO-NSAIDs; NSAIDs with an NO-releasing moiety) modulate PPARδ and offer the opportunity to revisit the controversial role of PPARδ in carcinogenesis (several papers report that PPARδ either promotes or inhibits cancer). This review summarizes the pharmacology of NO-NSAIDs, PPARδ cancer biology, and the relationship between the two. In particular, a study of the chemopreventive effect of two isomers of NO-aspirin on intestinal neoplasia in Min mice showed that, compared to wild-type controls, PPARδ is overexpressed in the intestinal mucosa of Min mice; PPARδ responds tom - andp -NO-ASA proportionally to their antitumor effect (p -> m -). This effect is accompanied by the induction of epithelial cell death, which correlates with the antineoplastic effect of NO-aspirin; and NO-aspirin's effect on PPARδ is specific (no changes in PPARα or PPARγ ). Although these data support the notion that PPARδ promotes intestinal carcinogenesis and its inhibition could be therapeutically useful, more work is needed before a firm conclusion is reached.